Correction: Crystal structure, magneto-structural correlation, thermal and electrical studies of an imidazolium halometallate molten salt: (trimim)[FeCl4]. Issue 28 (29th April 2020) - González-Izquierdo, Palmerina; Fabelo, Oscar; Beobide, Garikoitz; Cano, Israel; Ruiz de Larramendi, Idoia; Vallcorba, Oriol; Fernández, Jesús Rodríguez; Fernández-Díaz, María Teresa; de Pedro, Imanol
Abstract : Correction for 'Crystal structure, magneto-structural correlation, thermal and electrical studies of an imidazolium halometallate molten salt: (trimim)[FeCl4 ]' by Palmerina González-Izquierdo et al., RSC Adv., 2020, 10, 11200–11209. DOI: ; 10.1039/D0RA00245C .